2017
DOI: 10.1371/journal.pcbi.1005637
|View full text |Cite
|
Sign up to set email alerts
|

An optimal strategy for epilepsy surgery: Disruption of the rich-club?

Abstract: Surgery is a therapeutic option for people with epilepsy whose seizures are not controlled by anti-epilepsy drugs. In pre-surgical planning, an array of data modalities, often including intra-cranial EEG, is used in an attempt to map regions of the brain thought to be crucial for the generation of seizures. These regions are then resected with the hope that the individual is rendered seizure free as a consequence. However, post-operative seizure freedom is currently sub-optimal, suggesting that the pre-surgica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
250
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(278 citation statements)
references
References 82 publications
10
250
0
Order By: Relevance
“…Computational modelling of epilepsy surgery has received considerable attention in recent years with promising results (Goodfellow et al, 2016;Hebbink, Meijer, Huiskamp, van Gils, & Leijten, 2017;Jirsa et al, 2017;Lopes et al, 2017;Sinha et al, 2017;Terry, Benjamin, & Richardson, 2012). In this framework, neural masses or similar models are coupled through a patient-specific connectivity.…”
Section: Clinical Role Of Drsmentioning
confidence: 99%
“…Computational modelling of epilepsy surgery has received considerable attention in recent years with promising results (Goodfellow et al, 2016;Hebbink, Meijer, Huiskamp, van Gils, & Leijten, 2017;Jirsa et al, 2017;Lopes et al, 2017;Sinha et al, 2017;Terry, Benjamin, & Richardson, 2012). In this framework, neural masses or similar models are coupled through a patient-specific connectivity.…”
Section: Clinical Role Of Drsmentioning
confidence: 99%
“…We use the canonical theta model (Ermentrout et al, 1986, Lopes et al, 2017 which has been shown to capture relevant dynamics of neural mass models (Lopes et al, 2017); nodes can display transitions between "normal activity" (stable fixed point) and "epileptiform dynamics" (stable limit cycle) through a saddle node on invariant circle (SNIC) bifurcation. The dynamics of node ( = 1, … , ) is represented by its phase and obeys ̇( ) = (1 − cos ( )) + (1 + cos ( )) ( ) (1) where ( ) is the input current that the node receives from the other nodes in the network,…”
Section: Simulation Of Brain Dynamicsmentioning
confidence: 99%
“…(2) the term + is white uncorrelated Gaussian noise with mean = −1.2 and standard deviation 0.6, as used in previous studies (Lopes et al, 2017). is the ( , ) th entry of the adjacency matrix (i.e., the weighted correlation matrix of the functional network), is a global scaling factor that scales the network interactions compared to the noise, and is the stable fixed point of node ( ̇= 0 at = = 0).…”
Section: Simulation Of Brain Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior work has used global and nodal network measures to stratify surgical candidates and to select nodes for resection (Tomlinson, Porter, and Marsh 2017;Sinha et al 2016;Lopes et al 2017;Shah et al 2019) . Here we provide a simple algorithm to augment these methods by determining patient-specific confidence in the robustness of estimated statistics to small perturbations in spatial sampling.…”
Section: Jackknife Network Resampling Generates Confidence Intervals mentioning
confidence: 99%